Local biological effects of adipose stromal vascular fraction delivery systems after subcutaneous implantation in a murine model. (November 2016) - Vigani, Barbara; Mastracci, Luca; Grillo, Federica; Perteghella, Sara; Preda, Stefania; Crivelli, Barbara; Antonioli, Barbara; Galuzzi, Marta; Tosca, Marta C; Marazzi, Mario; Torre, Maria L; Chlapanidas, Theodora
The aim of this study was to test alginate beads and silk fibroin non-woven mats as stromal vascular fraction delivery systems to support cell implantation for tissue repair and regeneration, through trophic and immunomodulant paracrine signaling. Furthermore, in vivo scaffold biocompatibility was histologically analyzed in a murine model at different time endpoints, with particular focus on construct-induced vascularization and neoangiogenesis. The fibroin mat induced a typical foreign body reaction, recruiting macrophages and giant cells and concurrently promoted neovascularization of the implanted construct. Conversely, alginate beads triggered a more circumscribed, chronic inflammatory reaction, which decreased over time. The combined in vivo implantation of alginate beads and fibroin mat with stromal vascular fraction promoted vascularization and integration of scaffolds into the surrounding subcutaneous environment. The new blood vessel ingrowth should, hopefully, support engineered cell viability and functionality, as well as the transport of soluble bioactive molecules. Due to their neovascularization properties, stromal vascular fraction administration, using alginate or fibroin scaffolds, is a new, promising, cost-effective tissue engineering approach.